Strategi Komunikasi Pemasaran Berbasis Digital Dalam Memperkenalkan Destinasi Wisata Desa Suranadi Kabupaten Lombok Barat NTB - TUSTINI, I Gusti Ayu Ari; Suardana, Ketut Putu (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
Tourism has an increasingly important role in advancing the country's economy, contributing significantly to GDP. Indonesia, which is rich in natural and cultural beauty, attracts world tourists. Surandi Tourism Village, located in West Lombok Regency, is a promising tourist destination, famous for its serene natural beauty and rich culture. To take advantage of its potential, an effective digital marketing strategy is mandatory. Using social media platforms, official websites and digital campaigns, Surandi Tourism Village can expand its reach and attract the interest of potential tourists. By utilizing technology and creativity in marketing communications, it can strengthen its position as a leading tourist destination in Indonesia. This research describes concrete steps, from the use of social media to content development, that can be taken by the government and village communities to improve the image of Surandi Tourism Village in the tourism industry. Through digital marketing, Surandi Tourism Village can attract more visitors, strengthen the economy and preserve culture.